Endocytosis in the placenta: An undervalued mediator of placental transfer. (15th September 2021) - Cooke, Laura D.F.; Tumbarello, David A.; Harvey, Nicholas C.; Sethi, Jaswinder K.; Lewis, Rohan M.; Cleal, Jane K.
Abstract: Endocytosis is an essential mechanism for cellular uptake in many human tissues. A range of endocytic mechanisms occur including clathrin-dependent and -independent mechanisms. However, the role of endocytosis in the placenta and the spatial localisation of individual mechanisms is not well understood. The two principal cell layers that comprise the placental barrier to maternal-fetal transfer are the syncytiotrophoblast and fetal capillary endothelium. Endocytic uptake into the syncytiotrophoblast has been demonstrated for physiological maternal molecules such as transferrin-bound iron and low density lipoprotein (LDL) and may play an important role in the uptake of several other micronutrients, serum proteins, and therapeutics at both major placental cell barriers. These mechanisms may also mediate placental uptake of some viruses and nanoparticles. This review introduces the mechanisms of cargo-specific endocytosis and what is known about their localisation in the placenta, focussing predominantly on the syncytiotrophoblast. A fuller understanding of placental endocytosis is necessary to explain both fetal nutrition and the properties of the placental barrier. Characterising placental endocytic mechanisms and their regulation may allow us to identify their role in pregnancy pathologies and provide new avenues for therapeutic intervention. Highlights: Endocytosis contributes to placental uptake of maternal micronutrients and serum proteins. Endocytosis may have a role in placental uptake of viruses, drugs, and nanoparticles. The role of endocytosis in the placenta is understudied and needs further research.